2013
DOI: 10.2134/agronj2012.0432
|View full text |Cite
|
Sign up to set email alerts
|

Crop Productivity and Nutrient Dynamics in a Shrub‐Based Farming System of the Sahel

Abstract: Piliostigma reticulatum (DC.) Hochst., an indigenous shrub, forms an important vegetative component of parkland cropping systems in the Sahel; however, its biophysical interactions with soil and crops are not well understood. Therefore, the objectives were to determine the impact of P. reticulatum, under varying fertilizer rates, on crop yield response and soil nutrient dynamics. The experiment had a split-plot factorial design, where the main plot was shrub (presence or absence) and the subplot was fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
1
24
0
4
Order By: Relevance
“…This study has shown that intercropping and shrub residue application can have a substantial effect on microbial communities, with individual OTUs expressing high levels of enrichment in intercropping systems (9,10). Moving forward from these associations between individual OTUs and plant health status to the identification of microorganisms which might provide beneficial functions for improved crop growth will require the isolation and functional characterization of strains corresponding to the OTUs identified here.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This study has shown that intercropping and shrub residue application can have a substantial effect on microbial communities, with individual OTUs expressing high levels of enrichment in intercropping systems (9,10). Moving forward from these associations between individual OTUs and plant health status to the identification of microorganisms which might provide beneficial functions for improved crop growth will require the isolation and functional characterization of strains corresponding to the OTUs identified here.…”
Section: Discussionmentioning
confidence: 89%
“…Rhizosphere soils around amended shrubs show increased nutrient content (6), improved soil moisture profiles due to hydraulic lift (7), and a more diverse and complex microfauna soil food web (8). Intercropping with G. senegalensis (9) and P. reticulatum (10), with the incorporation of shrub residue, has also been shown to improve crop yields at two long-term field sites in Senegal.…”
mentioning
confidence: 99%
“…Une étude réalisée par Yelemou et al, (2007) sur la perception paysanne de Piliostigma reticulatum a révélé que 98% des personnes interrogées notent une croissance végétative meilleure et rapide lorsqu'un paillage de la culture est réalisé avec des feuilles de Piliostigma reticulatum. La présence et la gestion des arbustes dans les champs permet une amélioration notable du rendement de la céréale associée (Kizito et al, 2006 ;Abasse et al, 2013 ;Dossa et al, 2013 ;Binam et al, 2015). Les souches entretiennent des interactions positives avec la biomasse microbienne et agissent par conséquent sur la minéralisation du carbone et de l'azote se traduisant par des teneurs moyennes en carbone et azote totaux qui diminuent lorsqu'on s'éloigne des souches (Faye 2000 ;Wezel et al, 2000;Housman et al, 2007 ;.…”
Section: Resultatsunclassified
“…This happens at night when stomata close and water moves up through tap roots and is released to surrounding soil by surface roots. Indirect evidence from the study by [25], suggests that shrubs can assist crops through drought periods and [45] showed that under field conditions, there is no negative competition for water between shrubs and crops which in part was due to these two types of plants having roots in different layers of the soil. Obviously, in the current study using pots, hydraulic lift was not a factor and the roots of both shrubs and millet were exploring the same soil.…”
Section: Discussionmentioning
confidence: 99%
“…Hochst. (Caesalpiniaceae) in particular, have been identified as "resource islands" that promote growth of groundnut (Arachis hypogaea [25]); mango (Mangifera indica) [26]; and pearl millet (Pennisetum glaucum [27]). These shrub-crop systems have greater potential to sequester carbon at field scales than manure or compost amendments or trees [28] and promote soil bacterial and fungal diversity and activity [28] [29] [30] [31] and significantly reduce plant feeding nematodes [8].…”
Section: Introductionmentioning
confidence: 99%